Numerical modeling of an enhanced very early time electromagnetic (VETEM) prototype system. - Tie Jun Cui.
In this paper, two numerical models are presented to simulate an enhanced very early time electromagnetic (VETEM) prototype system, which is used for buried-object detection and environmental problems. Usually, the VETEM system contains a transmitting loop antenna and a receiving loop antenna, which run on lossy ground to detect buried objects. In the first numerical model, the loop antennas are accurately analyzed using the method of moments (MoM) for wire antennas above or buried in lossy ground. Then, the conjugate gradient (CG) methods, with the use of the fast Fourier transform (FFT) or MoM, are applied to investigate the scattering from buried objects. Reflected and scattered magnetic fields are evaluated at the receiving loop to calculate the output electric current. However, the working frequency for the VETEM system is usually low and, hence, two magnetic dipoles are used to replace the transmitter and receiver in the second numerical model. Comparing these two models, the second one is simple, but only valid for low frequency or small loops, while the first modeling is more general. In this paper, all computations are performed in the frequency domain, and the FFT is used to obtain the time-domain responses. Numerical examples show that simulation results from these two models fit very well when the frequency ranges from 10 kHz to 10 MHz, and both results are close to the measured data.
Keywords: Numerical analysis; Electromagnetic scattering; Environmental problems; Buried object detection; Time domain; Loop antennas; Magnetic dipoles; Method of Moments